Influence of hBN and MoS2 fillers on toughness and thermal stability of carbon fabric-epoxy composites (Fracture and Structural Integrity, 2022)
Hexagonal boron nitride (hBN) and molybdenum disulfide (MoS2) fillers of 2 to 8 wt.% influence on toughness, microhardness and thermal stability of carbon fabric-reinforced epoxy composite (CFREC) reported. Mode-I, mixed-mode I/II toughness and microhardness of CFREC improved due to the addition of hBN and MoS2 separately upto 6 wt.% filler loading. The epoxy matrix in CFREC modified by hBN and MoS2 strengthens the matrix, deflects the crack path and resists delamination. Toughness reduced beyond 6 wt.% filler addition due to agglomeration and poor fiber-filler-matrix bonding as revealed by the surface morphology of the fracture specimen. Thermal analysis reveals decomposition temperature at 25% weight loss increased from 395 to 430 °C and 395 to 411 °C due to 4 wt.% MoS2 and 4 wt.% hBN addition to CFREC respectively. Impermeable characteristics of MoS2 and hBN fillers caused tortuous diffusion path for gas molecules and delayed thermal decomposition.
Keywords: Molybdenum disulfide; Boron nitride; Fracture toughness; Thermal stability; Microhardness; Fracture surface morphology